Pengecualian Objek Pajak Penghasilan Wajib Pajak Badan Atas Dividen - Inas Syadza Wafikhoh (Jurist-Diction, 2022)
AbstractCurrently, the largest state revenue comes from the tax sector, and the income tax sector is a strategic sector to increase state revenue. One of the objects of income tax is dividends. Income tax is imposed on every additional economic received by the taxpayer. One of the subjects subject to income tax is a domestic entity called a domestic corporate taxpayer. Taxpayers who receive dividends are burdened with the obligation to pay income tax. Dividends are a type of income obtained from company profits that provide additional economic benefits. It turns out that the imposition of tax on dividends gives rise to double taxation, if more than one person is taxed on the same type of income. The imposition of double taxation can lead to tax avoidance. So in order to minimize the existence of this double tax, in the tax regulations there are exceptions to the type of income tax object which is strictly regulated in order to minimize the existence of double taxation.Keywords: Income Tax; Dividend; Double Taxation. AbstrakSaat ini pendapatan terbesar negara datang dari sektor pajak, dan sektor pajak penghasilan menjadi sektor strategis guna meningkatkan pendapatan negara. Salah satu objek pajak penghasilan adalah dividen. Pajak penghasilan dikenakan pada setiap tambahan ekonomis yang diterima oleh Wajib pajak. Subjek yang dikenakan pajak penghasilan salah satunya adalah badan dalam negeri yang disebut dengan wajib pajak badan dalam negeri. Wajib pajak yang mendapatkan dividen dibebani kewajiban untuk membayar pajak penghasilan Dividen merupakan jenis penghasilan yang didapatkan dari laba perusahaan yang memberikan tambahan ekonomis. Ternyata pengenaan pajak atas dividen, menimbulkan adanya pajak berganda, apabila lebih dari satu orang dikenai pajak atas jenis penghasilan yang sama Pengenaan pajak berganda ini dapat menimbulkan penghindaran pajak. Maka guna meminimalisir adanya pajak berganda ini, dalam peraturan perpajakan terdapat pengecualian jenis objek pajak penghasilan yang diatur secara tegas guna meminimalisir adanya pajak berganda.Kata Kunci: Pajak Penghasilan; Dividen; Pajak Berganda.